BAHASA KIASAN DALAM PUISI-PUISI KARYA WILLIAM BUTLER YEATS - SARDJONO, TRISATRIO SAMUEL (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2013)
Abstract The skripsi which is entitled â€œBahasa Kiasan dalam Puisi-Puisi Karya William Butler Yeatsâ€ aims at identifying and analyzing the types of figurative language that has been used by William Butler Yeats in his poems. Â The data were collected from the collections of The Wild Swans at Coole amongst many collections of William Butler Yeatsâ€™ poems and are analyzed descriptively by focusing on figurative language. Â The data are analyzed by using the intrinsic approach referring to Laurence Perrineâ€™s theory concerning the types of figurative language. The two purpose of literature are to entertain and educate its readers, by analyzing the figurative language containded in the William Butler Yeats poems, it will help the writer to understand the meaning of poem better and then it can provides the readers with the entertaining and educating experiences they need. Â The result of this skripsi shows that William Butler Yeats uses the figurative language to convey and clarify his purpose through his poem. There are seven types of figurative language found in William Butler Yeatsâ€™ poems. They are metaphor, simile, personification, synecdoche, symbol, overstatement, and irony. It was found that metaphors dominate the whole usage of figurative language in his poems. Â Â Keywords: Figurative Language, William Butler Yeatsâ€™ Poems, Intrinsic approach.